The making of New England, 1580-1643 - Drake, Samuel Adams, 1833-1905 (C. Scribner's Sons, 1896)
Originally published over 100 years ago, The Making of New England is Samuel Drake's engrossing compact description of the critical periods of discovery, exploration and settlement of New England from the earliest beginnings. He details a faithful record of the actions of forefathers and the home life of the pioneer settlers, illustrating how the country grew to be the great and prosperous nation it is today.